2020
DOI: 10.1111/acem.13931
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Emergency Physician Gestalt for Predicting Acute Appendicitis in Patients Age 5 to 20 Years

Abstract: Objectives Pediatric appendicitis remains a challenging diagnosis in the emergency department (ED). Available risk prediction algorithms may contribute to excessive ED imaging studies. Incorporation of physician gestalt assessment could help refine predictive tools and improve diagnostic imaging decisions. Methods This study was a subanalysis of a parent study that prospectively enrolled patients ages 5 to 20.9 years with a chief complaint of abdominal pain presenting to 11 community EDs within an integrated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…The area under the curve of 0.795 seems fair for a new disease with few specific clinical signs. Emergency physician gestalt has been studied in predicting other diseases and performed equally well, with an observed area under the curve of 0.83 for appendicitis in children, 30 0.75 for acute coronary syndrome, 31 0.86 for acute heart failure syndrome, 32 and 0.81 for pulmonary embolism. 33 In summary, in this large prospective cohort study of patients attending the ED for suspected COVID-19, anosmia, emergency physician estimate of high clinical probability, and bilateral B lines on lung ultrasonography increased the likelihood of identifying COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve of 0.795 seems fair for a new disease with few specific clinical signs. Emergency physician gestalt has been studied in predicting other diseases and performed equally well, with an observed area under the curve of 0.83 for appendicitis in children, 30 0.75 for acute coronary syndrome, 31 0.86 for acute heart failure syndrome, 32 and 0.81 for pulmonary embolism. 33 In summary, in this large prospective cohort study of patients attending the ED for suspected COVID-19, anosmia, emergency physician estimate of high clinical probability, and bilateral B lines on lung ultrasonography increased the likelihood of identifying COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in applying and teaching gestalt in emergency medicine. In many studies, physician gestalt demonstrates good performance in the diagnosis of pulmonary embolism 12–14 and appendicitis 15,16 . However, some studies have shown that physician gestalt is insufficiently accurate or safe to either rule in or rule out acute coronary syndrome 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, physician gestalt demonstrates good performance in the diagnosis of pulmonary embolism [12][13][14] and appendicitis. 15,16 However, some studies have shown that physician gestalt is insufficiently accurate or safe to either rule in or rule out acute coronary syndrome. 17 Physician gestalt also has been reported to be less accurate when compared with certain prediction tools in assessing shock and mortality in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…According to analysis, the Alvarado system score involve 8 different parameters and that could be useful for evaluating the health of the individual and planning of the treatment approach to improve health condition of patients. 8 For understanding the score the different parameters are applied that vary between 1 and 2. In addition to this, the summation of score is allowing the medical team for treatment modality.…”
Section: Introductionmentioning
confidence: 99%